Daumier : émigrants ou fugitifs ? - Jean-Philippe Chimot (Amnis)
Daumier left behind four painting and a landscape in small formats, completed between 1850 to 1870, entitled Emigrants or Fugitives. If the artist, who was sensitive to the aesthetic dimension of thecentury's dramas and conflicts, did not financially benefit from his public or private commands, he also avoided the optimistic lies of official viewings and the self-satisfaction of “elites”. In his sketched-out works, he interpreted emigration as a collective displacement, both troubling and uncertain. His manner and his material thus brought to light were fused with the historical weight of the immense voyages that his work alluded to so mysteriously.